TANDA GEJALA FISIK DAN PSIKOLOGIS SERTA PRESEPSI IBU DENGAN KEHAMILAN PALSU (PSEUDOCYESIS) - Yanti, Linda (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
A false pregnancy or pseudocyesis is an emotional and psychological condition of a woman who feels pregnant and develops common symptoms of pregnancy such as morning sickness, swollen breasts, enlarged belly. A case of false pregnancy or False pregnancy or pseudocyesis occurs in 6 of 22,000 pregnancies. This study aims to identify a false pregnancy or pseudocyesis associated with signs of symptoms and mother's perception. This research is a qualitative research with the design used is phenomenological. The population in this study were mothers who experienced false pregnancy (pseudocyesis) using the technique of acidental sampling, and 5 participants were added. In this study after all the data collected and then made transcripts in the program Nvivo for further analysis, categorization-categories that will produce the themes and made conclusions. The results showed signs of false pregnancy include no menstruation, enlarged abdomen, flecks, nausea, vomiting, enlarged hips, cravings, uterine movements and PP test (+) meanwhile for the mother's perception in this study can be seen in findings of interviews such as flat stomach, lost baby, taken supernatural / spirits, asked to shaman / smart people, believe in mystical things. Keywords: Symptom Signs, Mother's Perception, False Pregnancy (Pseudocyesis)